2018
DOI: 10.1002/ajpa.23638
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and cultural shifts of hunter‐gatherers of the Jomon period paralleled with environmental changes

Abstract: These temporal changes of diet and tooth ablation types occurred in parallel with climatic cooling and environmental change and help reveal how Holocene hunter-gatherers adapted to the changing environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…The reduction in sex-related differences to carbon and nitrogen isotopes at Tsukumo compared to O ̄ta, may further support more homogenised diets in the latter site due to food sharing (Kusaka et al 2010). Our sample was too small to assess sex-related differences in prevalence but a similar argument has been made at several Jomon sites, where similar diets have been shared across different sexes and identities (Yoneda et al 1996;Temple et al 2011;Kusaka et al 2018).…”
Section: Discussionmentioning
confidence: 69%
“…The reduction in sex-related differences to carbon and nitrogen isotopes at Tsukumo compared to O ̄ta, may further support more homogenised diets in the latter site due to food sharing (Kusaka et al 2010). Our sample was too small to assess sex-related differences in prevalence but a similar argument has been made at several Jomon sites, where similar diets have been shared across different sexes and identities (Yoneda et al 1996;Temple et al 2011;Kusaka et al 2018).…”
Section: Discussionmentioning
confidence: 69%
“…3200–2800 cal bp ) and the Inariyama shell mound from the Final Jomon period (ca. 3200–2200 cal bp ; Kusaka, Yamada, & Yoneda, in press) are located in the Aichi Prefecture of the Tokai region in eastern Japan. In this study, 38 individuals from Yoshigo and 17 from Inariyama were analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed Veth (2014) suggested that “such datasets…are being used as a mainstream proxy to explore archaeological trends and specifically demographic fluctuations” for some regions of Australia. Hence, the purpose and some of the key limitations of such modelling have been overlooked, with the end effect that the results may be uncritically treated as fact (e.g., Brockwell et al, 2017; Cook, 2019; Kusaka et al, 2018; Lancelotti et al, 2016; Lopez et al, 2019; McDonald, 2016; McDonald et al, 2018; Reynen et al, 2018; Tibby et al, 2018; Zeanah et al, 2017) and even used as foundational premises of further demographic frequency analysis. We explore some of these radiocarbon age‐based studies and some of their underlying premises below.…”
Section: Archaeology's Grand Challenges and The Role Of “Big Data”mentioning
confidence: 99%